Classic Christmas Collection - Trollope, Anthony (Saga Egmont, 2024)
Deep dive into this crackling collection of ‘Classic Christmas Stories’ from the very best writers around the world! We’ll start by dissecting Dickens’ moral message in the famous and festive ‘A Christmas Carol’, before whisking away to Russia as one man attempts to secure his fortune and fate at a party in ‘A Christmas Tree and a Wedding’. We’ll then encounter elves, demons, and dungeons in ‘A Kidnapped Santa Claus’ while witnessing two troubled couples attempt to give it all in ‘The Gift of the Magi’. Lastly, we’re all invited to ‘Christmas at Thompson Hall’ as one unsuspecting woman is forced to face the festive season with her long-lost ex-lover. There are family feuds, festive fights, and plenty of personal politics in this crackling collection of ‘Classic Christmas Stories’. Perfect for fans of ‘The Nightmare Before Christmas’. L Frank Baum (1856-1919) was an American author best known for his children’s books, particularly ‘The Wonderful Wizard of Oz’ and its sequels. Fyodor Dostoyevsky (1821-1881) was a Russian novelist and journalist. His works include ‘Crime and Punishment’, ‘The Idiot’, and ‘The Brothers Karamazov’. Charles Dickens (1812-1870) was an English writer and social critic, known for creating some of the world’s best-known fictional characters. His works include ‘Oliver Twist’, ‘David Copperfield’, and ‘Great Expectations’. Anthony Trollope (1815-1882) was an English novelist and civil servant of the Victorian era. His works include the ‘Chronicles of Barteshire’, ‘The Macdermots of Ballycloran’, and ‘The Warden’. O. Henry, the pen name of William Sydney Porter (1862-1910), was an American writer, celebrated for his short stories. His works include ‘The Gift of the Magi’, ‘The Duplicity of Hargraves’, and ‘The Ransom of Red Chief’.